HUBUNGAN PENENTUAN LOKASI USAHA TERHADAP PENJUALAN (Studi pada Pedagang Kaki Lima di Lokasi Pasar Comboran Kelurahan Sukoharjo, Kecamatan Sukun Malang) - Yaningwati, Fransisca (Profit: Jurnal Adminsitrasi Bisnis, 2007)
This paper tries to describe and to analize a correlation the place of work to a selling level. Basically, location ofÂ  workis essential factor in order to stimulate work success. Some variabels of place that influence the selling level, are easy to be seen, to be came, social and environment condition. Right place is as superior work asset. On the other hand wrong place will obstruct organization to catch their goals and profit. It can be clearly seen from this paper that social and environment condition is a dominant factor determining level of product selling. This reality does not mean that the enterpreneur ignore the other variabels in deciding place of their work